Implementasi Program Keluarga Harapan pada Masa Pandemi Covid-19 di Kabupaten Malang - Damayanti, Febriyana Hesti; Suroso, Titot Edy; Dwinugraha, Akbar Pandu (Jurnal Ilmiah Tata Sejuta STIA Mataram, 2022)
This study aims to examine the process of implementing the family of hope program during the Covid-19 pandemic involving government organizations as implementers and the community (KPM) as the target group. The method used is a descriptive research type with a qualitative approach with an inductive thinking pattern. The results showed that the implementation of PKH during the Covid-19 pandemic in Malang Regency which included PKH planning, initial meetings and PKH validation, determination of PKH KPM, distribution of PKH assistance funds, updating of PKH KPM data, verification of KPM commitments, PKH assistance has been running well for Adjusting the Minister of Social Affairs Regulation Number 1 of 2018, although there are several aspects that need to be optimized, including communication that is established at the planning stage, initial meetings and validation and verification of commitments that are not going well. PKH facilitators are required to be more assertive in carrying out their obligations to beneficiary families. Furthermore, it is necessary to apply information technology in the implementation of the distribution of PKH funds to make services faster, more precise and accurate.